Evaluation of meteorological parameters influence upon pollen spread in the atmosphere - Veriankaitė, Laura; Šaulienė, Ingrida; Bukantis, Arūnas (Journal of Environmental Engineering and Landscape Management, 2011)
The elements determining the meteorological conditions are the main parameters in processes of airborne pollen modeling. In modern research the influence of different meteorological element or their complex is analyzed basing upon the statistic methods or using dispersion models in which the possible influence of meteorological parameters upon airborne pollen is described in equations. The correlation of meteorological indicators and pollen concentration in the atmosphere fixed in Klaipėda Aerobiological Station is analyzed in this article. The coefficients of correlation of meteorological parameters and pollen concentration are calculated basing upon the Spearman's rank correlation method. The analysis of various factors was used for determining the complex influence of meteorological parameters upon the pollen concentration in the air. After evaluation of influence of meteorological parameters as separate factors one has determined that more than a half of analyzed pollen types showed statistically reliable (p < 0.05) correlation of pollen amount in the air and relative air humidity (89%), air temperature (74%) and amount of precipitation (52%). The investigation results showed that 37% of pollen amount of indicated plants genera and families in the atmosphere was determined by wind velocity. After evaluation of complex influence of meteorological factors on the concentration of pollen spread in the air one has determined that relative humidity and/or air temperature are one of the most significant environmental factors determining the amount of pollen in the atmosphere during the vegetation. Their influence was determined for all the three cases under study.Article in English.Meteorologinių parametrų įtakos žiedadulkių sklaidai atmosferoje įvertinimas Santrauka. Meteorologines sąlygas nusakantys elementai yra pagrindiniai parametrai modeliuojant žiedadulkių sklaidą. Nūdienos moksliniuose tyrimuose tam tikro meteorologinio elemento ar jų komplekso poveikis analizuojamas statistiniais metodaisarba taikant sklaidos modelius, kuriuose pagrindinėmis lygtimis aprašoma galima meteorologinių parametrų įtaka žiedadulkių sklaidai. Straipsnyje analizuojama meteorologinių rodiklių sąsajos su Klaipėdos aerobiologinėje stotyje fiksuota žiedadulkių koncentracija ore. Meteorologinių parametrų ir žiedadulkių koncentracijų koreliacijos koeficientai apskaičiuoti Spearman ranginės koreliacijos metodu. Tiriant kompleksinę meteorologinių parametrų įtaką žiedadulkių koncentracijai ore, išanalizuota įvairūs veiksniai. Atskirai įvertinus įvairių meteorologinių parametrų įtaką, nustatyta statistiškai patikima (p < 0,05) daugiau nei pusės analizuotų žiedadulkių tipų žiedadulkių kiekio ore ir santykinės oro drėgmės (89 %), oro temperatūros (74 %) ir kritulių kiekio (52 %) sąsaja. Tyrimo rezultatai rodė, kad vėjo greitis turi įtakos 37 % identifikuotų augalų genčių ir šeimų žiedadulkių kiekiui ore. Įvertinus kompleksinę meteorologinių veiksnių įtaką oru sklindančių žiedadulkių koncentracijai, nustatyta, kad santykinis drvgnumas ir/arba oro temperatūra yra vieni reikšmingiausių aplinkos veiksnių, lemiančių žiedadulkių kiekį atmosferoje vegetacijos metu.Reikšminiai žodžiai: žiedadulkės, oro temperatūra, santykinis drėgnumas, krituliai, vėjo greitis, daugiafunkcinė regresija.Оценка влияния метеорологических параметро вн адисперсию пыльцыв атмосфереРезюме. Элементы, описывающие метеорологические условия, являются основными параметрами в процессах моделирования дисперсии пыльцы. В современных исследованиях воздействие каждого метеорологического элемента илиих комплекса анализируется с помощью статистических методов и моделей распространения, в которых фундаментальными уравнениями описываются возможные эффекты воздействия метеорологических параметровна распространение пыльцы. Статья посвящена анализу соотношения метеорологических величин с концентрацией пыльцы, зафиксированной на аэробиологической станции Клайпеды. Коэффициенты корреляции междуметеорологическими параметрами и концентрацией пыльцы вычислены на основе метода ранговой корреляцииСпирмена. Анализ различных факторов был использован для определения комплексного влияния метеорологических параметров на концентрации пыльцы в воздухе. Оценка метеорологических параметров как отдельныхфакторов показала, что более половины анализируемых типов пыльцы свидетельствует о статистически значимой(р < 0,05) связи между пыльцой в воздухе и относительной влажностью (89 %), температурой воздуха (74 %) иосадками (52 %). Результаты исследования показали, что скорость ветра оказывает влияние на количество ватмосфере 37 % определенных семейств и родов пыльцы. Оценка комплексного влияния метеорологическихфакторов на концентрацию пыльцы в воздухе показала, что относительная влажность воздуха и(или) температуравоздуха являются одними из наиболее важных экологических факторов, определяющих количество пыльцы ватмосфере в течение вегетационного периода. Их влияние выявлено вo всех изученных случаях.Ключевые слова: пыльца, температуравоздуха, относительнаявлажность, осадки, скоростьветра, мультирегрессия.